An Explanation of RŪpakhandha in the Light of Science - วิชานาติ ศุภกาญจน์; งามจิตรเจริญ วัชระ; ปาลิภัทรางกูร คะนอง (Journal of Buddhist Studies Chulalongkorn University, 2020)
This research article aims to present a scientific explanation of the Buddhist teaching of Rūpa-khandha. The study finds that a possible scientific explanation of the doctrine of Rūpa-khandha is one that describes Rūpa-khandha or the body in a separate and reductive manner, starting from the smallest parts, and introducing the properties or behaviors of matter and energy in existing scientific knowledge in this explanation, especially in parts that do not concern abstract entities such as kamma, consciousness, and mental factors. According to the scientific conception, Rūpa-khandha or the body is simply matter and energy. It can be studied from the smallest parts of the body – the cells – to the tissues, organs, systems, and the entire body respectively. The structure and composition of the body and matters consist of the smallest entities, e.g., quarks. The body and matters may take one of the four states: solid, liquid, gas, or plasma. The nature of Rūpa-khandha or the body may be said to be subject to the law of the Three Characteristics, i.e. impermanence, suffering, and selflessness, that changes according to changing conditions. This is not unlike the constant movements according to the laws of thermodynamics and entropy which depict the occurrence, succession, degradation, and extinction of matter and energy. The research also finds that Rūpa-khandha exerts influence on the human body and mind, consistent with the scientific fact that matter and energy may affect human sentiments and daily life. Some of such influence may include stress, sleep, hormonal patterns, light, the four forces, as well as quantum physics.